IMPLEMENTASI SIPELDUK (SISTEM PELAPORAN DATA KEPENDUDUKAN) DALAM MENINGKATKAN EFISIENSI PELAYANAN PUBLIK DI KECAMATAN TANJUNGSIANG KABUPATEN SUBANG - melani, putri (LPPM UNSAP & FISIP UNSAP, 2025)
Current technological developments are very important for the implementation of government, in accordance with Subang Regent Regulation Number 75 of 2010 concerning the Main Duties, Functions and Work Procedures of Sub-districts in Subang Regency in realizing this policy, the Tanjungsiang Sub-district government created SIPELDUK (Population Data Reporting System), a digital village innovation that supports e-government by providing valid, accurate, and integrated population data between villages and sub-district levels in the Tanjungsiang area. Therefore, the purpose of this study is to determine how the implementation, obstacles, and efforts made in the management of SIPELDUK (Population Data Reporting System). The method used in this study is a qualitative research method with the objects of this study being 2 informants in Tanjungsiang District, 1 informant in Sindanglaya Village, and 1 informant in Sirap Village. The data collection techniques used are literature study, field study and triangulation. Furthermore, for data validity techniques with credibility test, transferability test, dependability test, and confirmability test. While for data processing, namely with data collection, reduction, data presentation, and conclusion. The results of this study found that the implementation of SIPELDUK (Population Data Reporting System) in Tanjungsiang District has not been fully implemented properly, although in terms of policy dimensions and objectives as well as the attitudes or tendencies (dispositions) of the implementers, these are appropriate, but there are still obstacles in terms of resources, characteristics of implementing agents, communication between implementing activity organizations, and the economic, social, and political environment. Although in its implementation there are still obstacles in the content of the policy, information in management, and support from implementers, there is an effort to overcome these obstacles. It is expected to improve the implementation of SIPELDUK (Population Data Reporting System), it is necessary to optimize technological infrastructure, increase human resource capacity, conduct periodic evaluation and monitoring, increase public awareness and conduct ongoing research on the evaluation of SIPELDUK (Population Data Reporting System) in order to find out or study the extent to which its implementation has been carried out.